Analisa Vegetasi Hutan Mangrove Di Selat Pogo-Pogo Kabupaten Halmahera Selatan - Laswi Irmayanti; Muhammad Nur; Sadam Husain M. Mayor; M Charis Kamarullah (Jurnal Ilmu Kelautan Kepulauan, 2019)
Mangrove ecosystems have a very important role for the coastal environment, both in terms of physical, ecological and economic. One of the important mangrove areas in South Halmahera is on the coast of Pogo-Pogo island. The purpose of this study was to identify the diversity and dominance of mangrove species in the Pogo-Pogo Strait. Research uses the method of the plot lanes. The types of mangroves found in the research location were 9 species, 3 of which were categorized as true mangrove and 6 types of asociate mangrove. The diversity of mangroves found at the study site was relatively low. The Shannon-Wienner species diversity index (H ') for seedling (H' = 0.59), sapling (H '= 0.00), and tree (H' = 0.66). This indicates that the distribution of individual numbers of each species was lowed and the stability of the mangrove forest community in the Pogo-Pogo strait was lowed. In all level of growth (seedlings, saplings and trees), the Rhizophora mucronata was the most dominating species.Key words: mangrove, diversity, pogo-pogo